Inteligência Artificial, Museus e Patrimônio: entrevista com Lucia Santaella - SILVA, Carmen Lucia Souza da (Universidade de Brasília, 2023)
Lucia Santaella is a CNPq researcher 1 A. She is a full professor in the Graduate Program in Communication and Semiotics at Pontifícia Universidade Católica de São Paulo (PUC- -SP), with a PhD in Literary Theory at PUC- -SP and a “Livre-Docência” in Communication Sciences at Escola de Comunicações e Artes of Universidade de São Paulo (ECA-USP). She is the Graduate Coordinator in Intelligence Technologies and Digital Design. She received the Jabuti Award in 2002, 2009, 2011 and 2014, the Sergio Motta, Liber Award, in Art and Technology, in 2005, and the Luiz Beltrão - academic maturity award, in 2010. Since 1996 she has been doing post-doctoral internships in Kassel, Berlin and Dagstuhl, Germany, under the auspices of DAAD/Fapesp. She has 51 published books, six of which are co-authored and two critical studies. She organized 26 books and published close to 500 articles in Brazil and abroad. Her most recent areas of research are: Communication, Cognitive and Computational Semiotics, Artificial Intelligence, Technological Aesthetics and Philosophy and Methodology of Science. In this interview, Lucia Santaella speak about Artificial Intelligence and the ongoing technological changes that affect Museums and Cultural Heritage, encompassing epistemological and social issues.